Evolution of Epoxides to Synthesize b-amino Alcohols: A Mini Review - Weng, Chenchen; Zhang, Hongyu; Xiong, Xiaoxia; Lu, Xiulian; Zhou, Yifeng (Asian Journal of Chemistry, 2014)
The present short review about a great deal of researches have been dedicated to the development of the reaction (catalyzing the ring opening of epoxide with amines for the corresponding amino-alcohols) in recent years.